Free Radical Scavenging and In vitro Cytotoxic Activity of Bugnay (Antidesma bunius) Leaves Extract against A549 Human Lung Adenocarcinoma and HCT-116 Human Colorectal Cancer Cell Lines - Geronimo, Arnold Joseph O.; Bancual, Mari Erika Joi F.; Ko, Karl Anthony L.; Soliba, Lycon Marie L.; Ildefonso, Jeric John C.; Soriano, Angelica Mae B.; Tagalog, Alta Christine Marie M.; Acosta, Nikolai E.; Ang, Vincent S.; Apigo, Mariebon A.; Buenconsejo, Dana Grace S.; Chan, Joanna Kaitlin G.; Gresh, Cassandra B.; Santos, Crisel B.; Buñag, Leo Emmanuel R.; Domantay, John Anthony A. (Indonesian Journal of Cancer Chemoprevention, 2020)
Cancer is one of the significant causes of mortality worldwide. Studies on antineoplastic drugs focused on natural products have revealed several mechanisms to inhibit cancer cells. Bugnay (Antidesma bunius) leaves showed potentials due to its activity observed against brine shrimp and breast cancer cells. However, there is still limited knowledge about its activity against other human cancer cells. This study focused on determining the phytochemical compounds in A. bunius leaves extract, the free radical scavenging activity of the extract using the Diphenylpicrylhydrazyl (DPPH) method, and in vitro cytotoxic activity against two cancer cell lines, namely HCT-116 human colorectal and A549 human lung adenocarcinoma cancer cell lines by using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The phytochemicals identified were unsaturated lactones, flavonoids, phenolics, diterpenes, saponins, tannins, carbohydrates, and reducing sugars. The extract showed significant free radical scavenging activity and a direct correlation of activity with concentration levels. It also exhibited cytotoxic activity against HCT-116 human colorectal and A549 human lung adenocarcinoma. Hence, A. bunius leaves have the potential to be a source of antioxidant and antineoplastic compounds. This warrant further isolation of the compounds for chemotherapeutic purposes.Keywords: Antidesma bunius, Bugnay, Cancer, Cytotoxicity, Radical